Розрахунок розподілу тиску природного газу по довжині похилого газопроводу з врахуванням фактора стискуваності - Лесовой, Л.; Близняк, Л. (Видавництво Національного університету "Львівська політехніка", 2002)
The analysis of an existing methods of calculating of pressure distribution of natural gas in a tilted conduit is indicated, influence of the factor of a compressibility of natural gas on pressure distribution in a conduit is shown and the accuracy of pressure distribution in a conduit disregarding modifications of the factor of a compressibility is indicated.
Keywords: 681.121